Lepidium meyenii Walp Exhibits Anti-Inflammatory Activity against ConA-Induced Acute Hepatitis - Wei Zheng; Shouwen Du; Mingyao Tian; Wang Xu; Yufei Tian; Tiyuan Li; Yanling Fu; Shipin Wu; Chang Li; Ningyi Jin (Hindawi Limited, 2018)
Strong inflammation is a prominent pathogenesis of acute hepatitis, which can induce hepatocyte death and lead to liver failure. Lepidium meyenii Walp (Maca) is a traditional herbal medicine mostly used in improving sperm motility and serum hormone levels, etc. However, there are no reports that showed Maca was designed for treating hepatitis so far. Therefore, the protective effects and pharmacological mechanisms of Maca are unknown in hepatitis. In this study, we found that the protective effects of Maca extract ameliorate ConA-induced acute hepatitis (CIH) and underlying mechanisms. We determined that pretreatment with Maca extract significantly suppressed the production of aminotransferases and inflammatory cytokines, including IFN-γ, TNF-α, IL-1β, IL-2, IL-6, IL-12, and IL-17a, and moderated acute liver injury in CIH. Maca recruited more myeloid-derived suppressor cells (MDSCs) to the liver and suppressed infiltration of natural killer T cells (NKT cells) and macrophages in the liver. Furthermore, our data indicated the molecular mechanism of the inhibitory inflammatory effects of Maca, which should suppress the activation of NF-κB, IFN-γ/STAT1, and IL-6/STAT3 signalings. Collectively, this present research explores Maca as an effective hepatoprotective medicine to inhibit inflammation and liver injury caused by acute hepatitis.